Antimicrobial and anticancer activities of Schiff base ligand and its transition metal mixed ligand complexes with heterocyclic base. (7th July 2017) - Abd El‐Halim, H. F.; Mohamed, Gehad G.; Anwar, Mahmoud N.
Abstract : A new Schiff base ligand (HL) was prepared via a condensation reaction of quinoline‐2‐carboxaldhyde with 2‐aminophenol in a molar ratio of 1:1. Its transition metal mixed ligand complexes with 1, 10‐phenanthroline (1, 10‐phen) as co‐ligand were also synthesized in a 1:1:1 ratio. HL and its mixed ligand complexes were characterized using elemental analysis, infrared, 1 H NMR, mass and UV–visible spectroscopies, molar conductance, magnetic measurements, solid reflectance, thermal analysis, electron spin resonance and X‐ray diffraction. Molar conductance measurements showed that all complexes have an electrolytic nature, except Cd(II) complex. From elemental and spectral data, the formulae [M(L)(1, 10‐phen)(H2 O)]Cl x ⋅ n H2 O (where M = Cr(III) ( x  =  n  = 2), Mn(II) and Ni(II) ( x  = 1, n  = 2), Fe(III) ( x  =  n  = 2), Co(II), Cu(II) and Zn(II) ( x  = 1, n  = 2)) and [Cd(L)(1, 10‐phen)Cl]⋅3H2 O for the metal complexes have been proposed. The geometric structures of complexes were found to be octahedral. Powder X‐ray diffraction reflected the crystalline nature of the complexes; however, the Schiff base is amorphous. HL and its mixed ligand complexes were screened against Gram‐positive bacteria ( Streptococcus pneumoniae and Bacillus subtilis ) and Gram‐negative bacteria ( Pseudomonas aeruginosa and Escherichia coli ). Antifungal activity was determined against Aspergillus fumigatus and Candida albicans, the data showing that most complexes had activity less than that of the Schiff base while Mn(II), Fe(III) and Ni(II) complexes showed no significant antifungal activity. The anticancer activity of HL and its metal complexes was also studied against breast and colon cell lines. The metal complexes showed IC50 higher than that of HL, especially the Cu(II) complex which showed the highest IC50 against breast cell line. Abstract : The relation between M─O bond strength and inhibition zone diameter of metal complexes.